KEANEKARAGAMAN JENIS PAKAN LEBAH MADU HUTAN (Apis spp) DI KAWASAN HUTAN LINDUNG DESA ENSA, KECAMATAN MORI ATAS, KABUPATEN MOROWALI UTARA - Siombo, Adriyanto; Labiro, Elhayat; Rahmawati, Rahmawati (Warta Rimba, 2014)
Research on the species diversity of food source trees for forest honey bee (Apis spp) has been conducted on protected forest at Ensa Village, Mori Atas Sub District, Mori Utara District.Â  The reasearch aimed at studying food source trees composition along with their diversity indeces for the honey bee.Â  The method used to analyse those vegetation was blocked line transect with sampling intensity of 6.25% covering an area of 16 ha that divided into five lines each with five observation plots.Â  The results of the research showed that there were 490 individuals from 43 species, 34 families, within which it was identified that 35 species from 30 families out of the are being food source trees for the honey bee.Â  The parts of the tree that is used as food were nectar and polen of tree flowers.Â  The diversity indeces (Hâ) for those species at tree, pole, sappling and seedling level, respectively, ofÂ  2.90, 2.94, 3.22, and 2.84.Â  As such, based on the identied indeces,Â  the diversity at tree, pole and seedling level are categorized as medium (1Hââ¤3) while for sappling level was high (Hââ¥3).Â  Overall, the species diversity for food source trees at the protected forest are abundantly available. Key Words : The diversity of feed, forest honey bees